PsycEXTRA Dataset 2012
DOI: 10.1037/e552082012-001
|View full text |Cite
|
Sign up to set email alerts
|

Public Housing Transformation and Crime: Making the Case for Responsible Relocation

Abstract: The research in this article examines the effect on crime rates of public housing transformation in Atlanta and Chicago, focusing

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
78
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(82 citation statements)
references
References 35 publications
3
78
1
Order By: Relevance
“…It may not be sensible, however, to rapidly accelerate and incentivise mobility to suburban jurisdictions, particularly without attending to the weaker social safety-net that Allard and Roth (2010) describe. Rather, it is more logical to engage in what Popkin et al (2012) term 'responsible relocation'. Popkin and colleagues suggest several aspects of housing policy that could constitute responsible relocation, including relocation counselling and follow-up supportive services, while expanding incentives to voucher households for locating in better neighbourhoods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It may not be sensible, however, to rapidly accelerate and incentivise mobility to suburban jurisdictions, particularly without attending to the weaker social safety-net that Allard and Roth (2010) describe. Rather, it is more logical to engage in what Popkin et al (2012) term 'responsible relocation'. Popkin and colleagues suggest several aspects of housing policy that could constitute responsible relocation, including relocation counselling and follow-up supportive services, while expanding incentives to voucher households for locating in better neighbourhoods.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, efforts to estimate the effect of vouchers on crime must account for the fact that voucher households disproportionately live in high-crime neighbourhoods and cities. and Popkin et al (2012) also examine the relationship between vouchers and crime in neighbourhoods. Ellen et al use longitudinal crime and voucher data from 10 US cities between 1997 and 2008.…”
Section: Empirical Evidencementioning
confidence: 99%
“…Ellen, Lacoe and Sharygin (2012) found that crime rose only after active foreclosures or real estate (lender)-owned properties reached a threshold number on the blockface. Popkin et al (2012) found that crime rates in neighbourhoods only rose in response to in-migration of former public housing residents who had been displaced from their demolished developments when their share exceeded a threshold.…”
Section: Policy Implicationsmentioning
confidence: 99%
“…For example, an evaluation of public housing demolitions in Atlanta, Georgia, as part of the Housing Opportunities for People Everywhere initiative, demonstrated that while public housing demolition was associated with overall crime reductions in the city, the decline was greater in areas where public housing was demolished and lower in areas where public housing residents relocated. 34 Additionally, our prior qualitative research, 35 and ethnographic studies conducted in Brooklyn, New York City, 36 and Denver, Colorado, 6 have reported an association between urban redevelopment and the displacement of drug activity.…”
Section: Introductionmentioning
confidence: 97%